Resurgent : how established organizations can fight back and thrive in an age of digital transformation - Birkinshaw, Julian M., 1964- (Bloomsbury Business, 2025)
A practical handbook examining how established businesses can use their unique advantages to fight back and win in a digital arena too often dominated by tech start-ups, disruptors and unicorns. The big tech companies (Alphabet, Amazon, Apple, Meta, Microsoft) have had an enormous impact on our everyday lives. A new wave of start-ups in the tech sector has dominated the press and swallowed up huge amounts of investment. But what about those established companies in the traditional parts of the world's economies, from energy, industrial and consumer goods to travel and health? They rarely got a mention. Everyone was talking about the disrupters – the start-ups and the entrepreneurs – and not about the incumbents. This book is a call for a reality check.